Design of Web-Based Promotion - Adeh Ratna Komala; H O Pakaya; I Ilhamdhani; N R Fauziyya (Universitas Komputer Indonesia, 2021)
The purpose of this study is to determine customer satisfaction by looking at the variables of interaction quality, system quality, and usability. This is done so that Chocolatier Dessert, as one of the desserts and snacks retailers, can compete and grow, so a website is designed to promote the goods produced. The method used the waterfall method, which works on the essence of a system that is done sequentially or linearly. The data was collected by distributing a list of questions to 50 respondents. The data collected was then processed using the SPSS application to test its validation and reliability. It is done to measure customer satisfaction and the variables that influence it. The results show that promoting the chocolatier through the website was very effective where the interaction quality and information system variables affected customer satisfaction, while usability did not. From the results of this study, it can be seen to maintain customer satisfaction. It is necessary to pay attention to the interaction system and information systems in promoting the Chocolatier Dessert.